Stress Distribution on Sandwich Structure with Triangular Grid Cores Suffered from Bending Load - Cui Xu; Huang Yanjiao; Wang Shou; Lu Chun; Fang Luping (International Journal of Aerospace Engineering)
Triangular grid reinforced by carbon fiber/epoxy (CF/EP) was designed and manufactured. The sandwich structure was prepared by gluing the core and composite skins. The mechanical properties of the sandwich structure were investigated by the finite element analysis (FEA) and three-point bending methods. The calculated bending stiffness and core shear stress were compared to the characteristics of a honeycomb sandwich structure. The results indicated that the triangular core ultimately failed under a bending load of 11000 N; the principal stress concentration was located at the loading region; and the cracks occurred on the interface top skin and triangular core. In addition, the ultimate stress bearing of the sandwich structure was 8828 N. The experimental results showed that the carbon fiber reinforced triangular grid was much stiffer and stronger than the honeycomb structure.